Climate change-driven ice variability and isotopic polarization in Antarctic coastal food webs - In Ok Lee; Junsung Noh; Hanna Bae; Hosang Kim; Dong-U Kim; Sung Joon Song; In-Young Ahn; Jong Seong Khim (Communications Earth & Environment)
Abstract Antarctic glacier retreat and changing sea ice extent are long-standing global issues, yet their ecological impact on coastal food webs remains unclear. We analysed stable isotopes of diets and consumers at five sites along Marian Cove during the 2018–2019 austral summer. Carbon isotope enrichment near the glacier differed from outer sites, reflecting environmental heterogeneity. Over the past decade, limpets’ primary diet shifted from micro- to macroalgae due to increased light penetration and glacial nutrient input. This study and literature reviews reveal contrasting Antarctic food web changes with sea ice polarization, warning of climatic crisis for coastal ecosystems.